(untitled) (CIPEEX, 2022)
THE PRESENT STUDY AIMS TO EVALUATE THE RATE OF ANTI-PGL-I SEROPOSITIVITY, THE SPECIFIC ANTIGEN FROM LEPROSY AGENT, AMONG INTERNS OF THE FORMER LEPROSY COLONY OF ANÁPOLIS, AND VOLUNTEERS FROM THE NEIGHBORHOOD, INCLUDING WORKERS OF THE INSTITUTION. MOREOVER, WE AIM TO RAISE AN EPIDEMIOLOGICAL STUDY OF THE INTERNS, ENUMERATING THE REASONS OF INTERNALIZATION AT THE INSTITUTION. IT IS AN OBSERVATIONAL, TRANSVERSAL STUDY AS A SCREENING OF PREVALENCE. THE FORMER COLONY IS KEPT UNDER THE NAME OF THE ORGANIZATION THAT RUNS IT SINCE 1981, MORHAN (MOVIMENTO DE REINTEGRAO DO HANSENIANO). ALTHOUGH IT ATTENDS DIVERSE CASES OF SOCIAL ABANDONMENT, NOT ONLY LEPROSY PATIENTS, IT STILL CARRIES THE STIGMA FROM THE TIMES OF LEPROSY COLONIES IN WHICH LEPROSY PATIENTS WERE MARGINALIZED, DISCRIMINATED BY SOCIETY AND FAMILY ITSELF. THERE ARE ABOUT 30 PATIENTS INTERNALIZED IN THE INSTITUTION NOWADAYS WITH DIVERSE ILLS SUCH AS LEPROSY, STROKE, SOCIAL ABANDONMENT, AMONG OTHERS. WE INCLUDED ALL CURRENT INTERNS OF THE FORMER COLONY OLDER THAN 18 YEARS OLD, AND WHO AGREED TO PARTICIPATE. ALL INDIVIDUALS WHO DECLINED PARTICIPATION OR UNDER 18 WERE EXCLUDED FROM THE STUDY. WE PERFORMED THE ML FLOW TEST, WHICH IS A IMMUNOCHROMATOGRAPHIC TEST TO DETECT IGM ANTIBODIES AGAINST PGL-I AND A PHYSICAL EVALUATION PERFORMED BY TWO TRAINED MEDICINE STUDENTS. THE ML FLOW RESULTS ARE OBTAINED AFTER 5 TO 10 MINUTES USING WHOLE BLOOD SAMPLES. WE TESTED 19 INDIVIDUALS IN THE FORMER LEPROSY COLONY (GROUP 1) AND 21 INDIVIDUALS LIVING IN THE NEIGHBORHOOD (GROUP 2). OBTAINED RESULTS POINTED TO 3 SEROPOSITIVE INDIVIDUALS IN THE GROUP 1, INDICATING A POSITIVITY OF 15,8% IN THIS GROUP. IN GROUP 2, ONLY 1 INDIVIDUAL WAS POSITIVE TO ML FLOW TEST, RESULTING IN A POSITIVITY OF 4%. INTERESTINGLY WE COULD NOT FIND A BCG SCAR IN NO ONE OF THE POSITIVE INDIVIDUALS, AND NO SMEARS COULD BE FOUND IN PHYSICAL EVALUATION IN ONE POSITIVE INDIVIDUAL. THE PRESENT STUDY SUPPORTS THE ELUCIDATION OF EPIDEMIOLOGICAL, CLINICAL OR SOCIAL ASPECTS OF THE DISEASE, AIMING AT A HUMANITARIAN FORMATION OF THE HEALTHCARE WORKER. ML FLOW POSITIVITY AMONG MORHAN INTERNS CORRELATES WITH THAT FOUND AMONG PATIENTS AND CONTACTS OF LEPROSY PATIENTS. IN FUTURE STEPS, THE PRESENT PROJECT AIMS TO INCREASE THE NUMBER OF PARTICIPANTS IN EACH GROUP AND INCLUDE INDIVIDUALS LIVING IN FARTHER NEIGHBORHOODS. THIS COMPARISON MAY INSTANTIATE ACTIVITIES TO BREAK SOCIAL STIGMA AND PREJUDICE OVER THE DISEASE AND ITS PATIENTS.